Knowledge of Hepatitis B Vaccine among Operating Room Personnel in Nigeria and Their Vaccination Status. (19th October 2011) - Kesieme, Emeka B.; Uwakwe, Kenechi; Irekpita, Eshiobo; Dongo, Andrew; Bwala, Kefas John; Alegbeleye, Bamidele J.
Abstract : Background . Hepatitis B virus (HBV) infection is a well recognised occupational health hazard preventable by vaccination. Objectives . To determine the knowledge of operating room personnel (ORP) in Nigeria about the Hepatitis B vaccine, their perception of Hepatitis B vaccination and vaccination status against HBV. Methods . Four university hospitals were selected by simple random sampling. A structured questionnaire was administered to 228 ORP after obtaining consent. Result . Only 26.8% of ORP were vaccinated against HBV. The primary reason for not being vaccinated or for defaulting from vaccination was lack of time. Differences in age, sex, duration of practice and respondent's institution between vaccinated and unvaccinated ORP were not significant (P > 0.05 ). The majority (86.8%) had the awareness of the existence of Hepatitis B vaccine. 83.8% of respondents believed that the vaccine should be given to the ORP as part of work place safety measures. The majority were aware of the modes of transmission of HBV infection. 78.9% of respondents believed that Hepatitis B vaccine is safe and 81.1% would recommend it to another staff. Conclusion . Despite a good knowledge about HBV infection and vaccine, most of ORP are still not vaccinated. Hepatitis B vaccination should be a prerequisite for working in the theatre, hence putting surgical patients at reduced risk.